The Information Searching Behaviour of Music Directors - Chandler, Martin (Evidence Based Library and Information Practice)

(untitled) (University of Alberta Library, 2019)
Objective – This research project sought to elucidate some of the information searching behaviours of directors/conductors of performing music ensembles when selecting repertoire for performance. Of particular focus was the kind of information needed to select repertoire and where that information was sought and acquired.Methods – Semi-structured, guided interviews were undertaken with three conductors from varying musical ensemble forms (choral, orchestral, and wind). This included a graphical elicitation exercise following Sonnenwald’s concept of information horizon maps. A narrative analysis was done, and recurring themes were sought in the various responses to questions and created drawings.Results – The results indicated that directors make significant use of historical and print resources in creating personal lists of repertoire for current or future use. Professional connections for discussion of new or less well-known repertoire were also very important. One particularly interesting outcome was the non-temporally bound nature of conductors’ information searching behaviour, as the current models of information behaviour primarily relate to temporally bound searches. The Internet was noted by the three conductors not as an information source in and of itself but rather as an extension of other information sources.Conclusions – This research highlighted the atemporal nature of information searching behaviour in music directors and suggested a similar aspect in the broader information search process. It indicated a need for libraries that cater to performers to maintain historical lists of varying types (e.g., concert programs, similar lists created by other prominent members of the community, and other types of repertoire lists). Additionally, maintaining community connections and knowledge of new or newly available repertoire is important.